Land, Art and Activism in Galician Writing by Women: Teresa Moure's A intervencin (2010) - Barbour, Catherine (Legenda - Modern Humanities Research Association, 2023)
If small literatures have been consistently banished to the margins of history, their women’s voices have been doubly silenced. Narrative by women writing in the language of Galician from the non-state Atlantic nation of Galicia in north-western Spain represents a case in point, demonstrating the persistent and multifaceted tensions between language, nation, gender and genre. In this essay, through analysis of the 2010 novel A intervención [The Intervention] by influential writer Teresa Moure (born Monforte de Lemos, 1969), I examine how creativity is presented as a form of resistance to the heteropatriarchal neoliberal order of the nation-state, demonstrating how women in minoritised linguistic and cultural contexts write against the hegemonic social, political, environmental and economic discourses that have endeavoured to stifle them. Defying the binds relating to their linguistic, cultural and literary heritage, as well as their gender, many contemporary women writers of fiction in Galician have set out to defy state hegemony and reclaim space in the historically patriarchal Galician literary sphere, renegotiating and redefining discourses of Galician culture more generally.
Contested Communities: Small, Minority and Minor Literatures in Europe
PUBLISHED
Studies in Comparative Literature 57 Review: 'In the third chapter, Catherine Barbour examines the 2010 novel by Galician author Teresa Moure, A intervencin, through the prism of ecology and `artivism, a Chicano-inspired `conscious intermingling of art and political activism (43), thereby offering unique perspectives on minority identity in this corner of the Atlantic.' https://occt.web.ox.ac.uk/occt-review#collapse5175636
Cambridge
Keywords: Identities in Transformation; Inclusive Society